Psychological Disorder of George Harvey as Seen in the Lovely Bones - Adelya Fajarwati (Lexicon, 2012)
This graduating paper discusses the psychological disorder found in the character Mr. Harvey. The objectives of this paper are to find out the cause that could make Mr. Harvey as a killer and also a rapist and, to study the childhood memories that influence his behavior in the development of his personality.This study applies library research method. The data and other supporting references are gained from library and websites. This study uses Psychoanalytic Approach to find psychological disorder in analyzing the character, Mr. Harvey, and the coherence of every evidences that show Mr. Harvey’s background.In this study the present writer finds that it is the traumatic experience of Mr. Harvey that makes him suffer from psychological disorder. The types of psychological disorder found in the character are; Post-Traumatic Stress Disorder (PTSD), Antisocial Personality Disorder (ASPD), and Pedophilia.